2022
DOI: 10.1177/00302228221120123
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation among Adolescents: A Case of Bullying Victimization and Emotional Intelligence

Abstract: This paper attempted to examine suicidal ideation among adolescents in terms of bullying victimization and emotional intelligence. It had been observed that adolescents have to face the challenge of suicidal ideation through bullying and reduce it through emotional intelligence. A sample of 1017 adolescents was sampled from public sector primary schools in the district of Gujrat, Punjab, Pakistan to conduct the cross-sectional survey. For this study, the scale of bullying victimization (Illinois Bullying Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Using bullying victimization, emotional intelligence, and suicidal ideation as a perspective, this article attempted to study suicidal ideation in teenagers by N. Kausar et al, [33] In the Gujrat district of the Punjab region to gather information from adolescents, the researchers chose the Teacher's Screening Items, Consent Form, Demo-graphic Form, Illinois Bullying Scale (Espelage & Holt, 2001), Emotional Intelligence Scale for Children and Adolescents (Batool & Hayat, 2018), and Suicidal Ideation Attributes Scale. Software for data analysis, such as SPSS and MS Excel was used.…”
Section: Authorsmentioning
confidence: 99%
“…Using bullying victimization, emotional intelligence, and suicidal ideation as a perspective, this article attempted to study suicidal ideation in teenagers by N. Kausar et al, [33] In the Gujrat district of the Punjab region to gather information from adolescents, the researchers chose the Teacher's Screening Items, Consent Form, Demo-graphic Form, Illinois Bullying Scale (Espelage & Holt, 2001), Emotional Intelligence Scale for Children and Adolescents (Batool & Hayat, 2018), and Suicidal Ideation Attributes Scale. Software for data analysis, such as SPSS and MS Excel was used.…”
Section: Authorsmentioning
confidence: 99%
“…[3] One recent study found that bullying victimization and low emotional intelligence were associated with suicidal ideation among adolescents. [4] This highlights the need for interventions to address bullying victimization and emotional intelligence to prevent suicidal ideation among young people. In addition to the negative effects on mental health, bullying victimization can also negatively affect academic achievement and school attendance.…”
Section: Introductionmentioning
confidence: 99%
“…The study also found that socio-cultural, contextual, and socio-economic variations in the sub-region could contribute to bullying victimization. The post-conflict dynamics in Sierra Leone could trigger compulsive behaviours in school-going adolescents who may still have social exclusion through turbulent moments [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, to the negative effects on mental health, research has indicated that adolescents who skip school or drop out are more likely to become victims of bullying and this can have long-term consequences for their future opportunities and well-being. [6], Addressing bullying victimization in schools is therefore important for young people's mental health, academic success, and future prospects. Many interventions can be used to address bullying victimization among in-school adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation